Modeling and Pedagogy - Jovanovska , Sashka (Indonesian Journal of Education Methods Development, 2020)
The depth of knowledge a student will develop while building a model, the memories and skills they will gain that transcend content, and the teamwork they will develop during the process are just a few of the benefits of the modeling process. Ultimately, the modeling process will allow students and teachers to experience education in a way that matches the way work is done in scientific research, engineering, and other professional settings. Having students build models to solve problems is an enormous goal and enormous goals require enormous planning. The purpose of this guide is to outline the pedagogical approaches a teacher will need to lead their students on the journey from novice modelers to expert modelers